2014
DOI: 10.3389/fendo.2014.00211
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Regulation of Bone Regeneration: Theories, Models, and Experiments

Abstract: How mechanical forces influence the regeneration of bone remains an open question. Their effect has been demonstrated experimentally, which has allowed mathematical theories of mechanically driven tissue differentiation to be developed. Many simulations driven by these theories have been presented, however, validation of these models has remained difficult due to the number of independent parameters considered. An overview of these theories and models is presented along with a review of experimental studies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 86 publications
(134 reference statements)
2
48
0
1
Order By: Relevance
“…A primary limitation, when considering both the mechanical and biological aspects, is that is it necessary to solve a series of PDEs and formulate a FE implementation within an iterative procedure (Isaksson, 2012, Anderson et al, 2014, Betts and Müller, 2014). …”
Section: Mechanobiological Modelingmentioning
confidence: 99%
“…A primary limitation, when considering both the mechanical and biological aspects, is that is it necessary to solve a series of PDEs and formulate a FE implementation within an iterative procedure (Isaksson, 2012, Anderson et al, 2014, Betts and Müller, 2014). …”
Section: Mechanobiological Modelingmentioning
confidence: 99%
“…In the absence of cortical contact and with the use of locking screws, the stiffness of the bone–implant construction is almost exclusively defined by the load transfer through the interlocking screws. This assembly is subjected to a complex physiological loading, which may be analyzed as a combination of three main types of load: pure shear and torsion, which create a nonuniform shear loading within the tissue; axial compression; and bending forces, which result in compression on one side and tension on the other side . As previously mentioned, the screws engaging the bone cortices aim to counteract rotational, axial, and bending forces and stabilize the bone–implant construct.…”
Section: Reduced Screw‐to‐nail Compliancementioning
confidence: 99%
“…As reported by Penzkofer et al ., shear movements at the fracture site may tend to damage the inner cortex and may also produce increased play between the nail and the surrounding bone. With regard to bending loading, it has been shown that it may result in asymmetric callus formation, where healing may be considerably inhibited on the tensile side of the callus and promoted on the compressive side . In the screw‐to‐bone toggling‐reduction methods previously described, the increase in the overall fixation system stiffness constructively reduced unfavorable (e.g., shear and torsion) interfragmentary movements that are detrimental to fracture healing; however, they also reduced the beneficial compression movements at the fracture site.…”
Section: Reduced Screw‐to‐nail Compliancementioning
confidence: 99%
See 2 more Smart Citations